PENGUKURAN TINGKAT KEMATANGAN DAN REKOMENDASI PERBAIKAN LAYANAN TEKNOLOGI INFORMASI INSTITUSI MENGGUNAKAN COBIT 2019 DAN ITIL 4 - YAHYA, DARIS; UMAROH, SOFIA; P, KURNIA RAMADHAN (e-Proceeding FTI, 2024)
The National Institute of Technology is an educational institution that pays attention to the importance of IT governance by having an Information and Communication Technology Technical Implementation Unit (UPT-TIK). In managing problems, UPT-TIK Itenas must maximize the organizational management by assessing risks properly, making it possible to manage problems that occur optimally. In this study, COBIT 2019 (Control Objective for Information and Related Technology) was used to measure the maturity level of IT domains DSS03 (Managed Problems) and ITIL 4 (Information Technology Infrastructure Library) to design Value Streams at UPT-TIK Itenas. The measurement results obtained a maturity value of 2.33 at maturity level 2 (Managed) with a target maturity value of 3.00 at maturity level 3 (Defined). These results are used as a reference in designing a Value Streams and SOP (Standard Operating Procedure) as a reference in managing problems in Itenas in carrying out and providing educational services. Abstrak Institut Teknologi Nasional merupakan instansi pendidikan yang memerhatikan pentingnya tata kelola TI dengan memiliki Unit Pelaksana Teknis Teknologi Informasi dan Komunikasi (UPT-TIK). Dalam mengelola permasalahan, UPT-TIK Itenas harus memaksimalkan pengelolaan manajemen organisasi dengan menilai risiko dengan baik, memungkinkan untuk mengelola permasalahan yang terjadi secara optimal. Dalam penelitian ini, digunakan COBIT 2019 (Control Objective for Information and Related Technology) untuk mengukur tingkat maturity TI domain DSS03 (Managed Problems) dan ITIL 4 (Information Technology Infrastructure Library) untuk merancang Value Stream di UPT-TIK Itenas. Hasil pengukuran diperoleh nilai maturity 2,33 pada maturity level 2 (Managed) dengan target nilai maturity 3,00 pada maturity level 3 (Defined). Hasil tersebut dijadikan acuan dalam merancang Value Streams dan SOP (Standard Operating Procedure) sebagai acuan dalam melakukan pengelolaan permasalahan di Itenas dalam menjalankan dan menyediakan layanan pendidikan.